Designing a hybrid thin-film/wafer silicon triple photovoltaic junction for solar water splitting - Paula Perez-Rodriguez and Wouter Vijselaar and Jurriaan Huskens and Machiel Stam and Michael Falkenberg and Miro Zeman and Wilson Smith and Arno H.M. Smets (Progress in photovoltaics, 2019)
Solar fuels are a promising way to store solar energy seasonally. This paper proposes an earth-abundant heterostructure to split water using a photovoltaic-electrochemical device (PV-EC). The heterostructure is based on a hybrid architecture of a thin-film (TF) silicon tandem on top of a c-Si wafer (W) heterojunction solar cell (a-Si:H (TF)/nc-Si:H (TF)/c-Si(W)) The multijunction approach allows to reach enough photovoltage for water splitting, while maximizing the spectrum utilization. However, this unique approach also poses challenges, including the design of effective tunneling recombination junctions (TRJ) and the light management of the cell. Regarding the TRJs, the solar cell performance is improved by increasing the n-layer doping of the middle cell. The light management can be improved by using hydrogenated indium oxide (IOH) as transparent conductive oxide (TCO). Finally, other light management techniques such as substrate texturing or absorber bandgap engineering were applied to enhance the current density. A correlation was observed between improvements in light management by conventional surface texturing and a reduced nc-Si:H absorber material quality. The final cell developed in this work is a flat structure, using a top absorber layer consisting of a high bandgap a-Si:H. This triple junction cell achieved a PV efficiency of 10.57%, with a fill factor of 0.60, an open-circuit voltage of 2.03 V and a short-circuit current density of 8.65 mA/cm 2 . When this cell was connected to an IrO x /Pt electrolyser, a stable solar-to-hydrogen (STH) efficiency of 8.3% was achieved and maintained for 10 hours.
Keywords: electrolysis; heterostructures; hydrogen fuel; multijunction; open-circuit voltage; photovoltaic